How can mobile applications support suicide prevention gatekeepers in Australian Indigenous communities?. (August 2020) - Brown, Kelly; Toombs, Maree; Nasir, Bushra; Kisely, Steve; Ranmuthugala, Geetha; Brennan-Olsen, Sharon L.; Nicholson, Geoffrey C.; Gill, Neeraj S.; Hayman, Noel S.; Kondalsamy-Chennakesavan, Srinivas; Hides, Leanne
Abstract: Rationale: Suicide prevention training in Aboriginal and Torres Strait Islander communities is a national health priority in Australia. Objective: This paper describes a qualitative study to increase understanding of how a mobile application (app) could be used to support suicide prevention gatekeepers in Indigenous communities. We respectfully use the term Indigenous to refer to Australian peoples of Aboriginal and/or Torres Strait Islander descent. Method: Two participatory design workshops were held with 12 participants who were either Indigenous health workers or community members. The workshops first explored what knowledge, skills, and support suicide prevention gatekeepers in Indigenous communities may require, as well as how technology, specifically mobile apps, could be used to support these needs. Results: Qualitative analysis identified four themes related to perceptions of who gatekeepers are, their role requirements, technology and supporting resources, as well as broader community issues. Participants thought training programs should target key, accessible, and respected people from diverse, designated, and emergent groups in Indigenous communities to act as gatekeepers, but requested an alternative, more culturally appropriate term to 'gatekeeper' (e.g., responder). Training should prepare gatekeepers for multifaceted suicide prevention roles, including the identification and management of at-risk Indigenous persons, the provision of psychoeducation and ongoing support, as well as facilitate integrated care in collaboration with community services. A combination of multiple support resources was recommended, including multi-platform options in the technology (e.g., mobile applications, social media) and physical domains (e.g., wallet cards, regular meetings). Recommended app features included culturally appropriate refresher content on suicide intervention, training recall, integrated care, how to access gatekeeper peer support, and debriefing. Broader community concerns on gatekeeper support needs were also considered. Highlights: Qualitative study explores new suicide prevention tools for Indigenous Australians. Multi-platform technology and physical gatekeeper support resources recommended. Key app functions include suicide intervention, refresher training, and referral. Gatekeeper/responder selection criteria and training recommendations are provided.